Hematological and Biochemical Factors Predicting SARS Fatality in Taiwan - Hsiao-Ling Chang; Kow-Tong Chen; Shu-Kuan Lai; Hung-Wei Kuo; Ih-Jen Su; Ruey S. Lin; Fung-Chang Sung (Journal of the Formosan Medical Association, 2006)
Severe acute respiratory syndrome (SARS) has a high fatality rate worldwide. We examined the epidemiologic and clinical factors associated with death for all laboratory-confirmed SARS patients in Taiwan. Methods: Using initial data in medical records reported by hospitals to the Center for Disease Control in Taiwan, we analyzed whether hematological, biochemical and arterial blood gas measures could predict fatality in 346 SARS patients. Results: Both fatalities (n = 73; 21.1%) and survivors had elevated plasma concentration of initial C-reactive protein (CRP), but the mean CRP concentration was higher in fatalities (47.7 ± 43.3 mg/L) than in survivors (24.6 ± 28.2 mg/L). Initial lymphocyte counts were low in both fatalities (814 ± 378/μL) and survivors (1019 ± 480/μL). After controlling for age and sex, multiple logistic regression analysis showed that hematological factors significantly associated with fatality included initial neutrophil count > 7000/μL (odds ratio [OR] = 6.4), initial CRP concentration > 47.5 mg/L (OR = 5.8) and lactic acid dehydrogenase (LDH) > 593.5 IU/L (OR = 4.2). Factors significantly associated with initial CRP concentration > 47.5 mg/L included dyspnea (OR = 4.3), red blood cell count < 4.1 × 106/μL (OR = 4.3) and serum aspartate amino-transferase > 57 IU/L (OR = 3.1). Conclusion: Initial neutrophil count, CRP and LDH levels are important predictors of mortality from SARS. [J Formos Med Assoc 2006;105(6):439-450]